PERAN HOMESTAY DALAM PENGEMBANGAN EKONOMI DAN PARIWISATA DESA MARGALUYU, PENGALENGAN, JAWA BARAT - Yuliani, Nafisah; Trisnawati, Nana; Idaman, Nur; Budilaksono, Sularso; Suryani, Fitri; Marhalinda, Marhalinda; Suwartane, I Gede Agus (Jurnal Abdi Insani, 2024)
The problems of community service partners in Margaluyu Pengalengan Village, West Java are: optimizing homestay management, product development and tourist attractions, marketing and promotion, involvement of local communities. The aim of community service is: identifying homestay opportunities generated for the local community of Margaluyu Village, Pengalengan, exploring the potential of homestays in the Margaluyu Village area, Pengalengan, exploring the role of homestays in the economic and tourism development of Margaluyu Village, Pengalengan. Improvements that have been made by homestay owners require support from the government and related agencies in providing tourist village infrastructure. Local governments are working with villagers to improve accessibility, repair roads, provide clean water sources, and improve sanitation. Apart from that, other supporting facilities have also been improved, such as providing stable electricity and adequate internet access. This provides long-term benefits for village communities and strengthens the attractiveness of the Situ Cipanunjang Tourism Village, Margaluyu Pengalengan Village, West Java. Thus, the role of homestays in economic development in Margaluyu Pengalengan Village, West Java, Pengalengan, is very significant. Apart from providing a direct economic impact through increasing people's income, homestays are also a catalyst for infrastructure development, community empowerment and promotion of local products. With the right support from various related parties, homestays can become one of the main driving forces in developing the local economy and improving community welfare in Margaluyu Pengalengan Village, West Java.